Evaluation of sublethal effects of polymer-based essential oils nanoformulation on the german cockroach - Werdin Gonzalez, Jorge Omar (2016)
The German cockroach, Blattella germanica (L.), is a serious household and public health pest worldwide. The aim of the present study was to evaluate the sublethal activity of polymer-based essential oils (EOs) nanoparticles (NPs) on adults of B. germanica. The LC50 and LC25 for contact toxicity were determined. To evaluate the repellency of EOs and NPs at LC25, a software was specially created in order to track multiple insects on just-recorded videos, and generate statistics using the obtained information. The effects of EOs and NPs at LC25 and LC50 on the nutritional physiology were also evaluated. The results showed that NPs exerted sublethal effects on the German cockroach, since these products enhance the repellent effects of the EOs and negatively affected the nutritional indices and the feeding deterrence index.